A novel therapeutic peptide targeting myocardial reperfusion injury. Issue 3 (30th May 2019) - Boisguérin, Prisca; Covinhes, Aurélie; Gallot, Laura; Barrère, Christian; Vincent, Anne; Busson, Muriel; Piot, Christophe; Nargeot, Joël; Lebleu, Bernard; Barrère-Lemaire, Stéphanie
Abstract: Aims: Regulated cell death is a main contributor of myocardial ischaemia-reperfusion (IR) injury during acute myocardial infarction. In this context, targeting apoptosis could be a potent therapeutical strategy. In a previous study, we showed that DAXX (death-associated protein) was essential for transducing the FAS-dependent apoptotic signal during IR injury. The present study aims at evaluating the cardioprotective effects of a synthetic peptide inhibiting FAS:DAXX interaction. Methods and results: An interfering peptide was engineered and then coupled to the Tat cell penetrating peptide (Tat-DAXXp). Its internalization and anti-apoptotic properties were demonstrated in primary cardiomyocytes. Importantly, an intravenous bolus injection of Tat-DAXXp (1 mg/kg) 5 min before reperfusion in a murine myocardial IR model decreased infarct size by 48% after 24 h of reperfusion. In addition, Tat-DAXXp was still efficient after a 30-min delayed administration, and was completely degraded and eliminated within 24 h thereby reducing risks of potential side effects. Importantly, Tat-DAXXp reduced mouse early post-infarction mortality by 67%. Mechanistically, cardioprotection was supported by both anti-apoptotic and pro-survival effects, and an improvement of myocardial functional recovery as evidenced in ex vivo experiments. Conclusions: Our study demonstrates that a single dose of Tat-DAXXp injected intravenously at the onset of reperfusion leads to a strong cardioprotection in vivo by inhibiting IR injury validating Tat-DAXXp as a promising candidate for therapeutic application. Graphical Abstract: